Clinical Identifiers, Comorbidities, and Outcomes among COVID-19 Confirmed Patients in Banda Aceh, Indonesia - Yanti, Budi; Zulfikar , T.; Afrina, Devi; Agustika, Rudi (Institute of Topical Disease Universitas Airlangga, 2022)
Coronavirus disease 2019 (COVID-19) is a highly contagious disease with an increasing number of infections in Indonesia. However, hypertension and diabetes are chronic diseases with high incidence in Aceh, there is still limited information regarding the demographics and clinical data of COVID-19 patients. This study aims to explain the clinical characteristics, comorbidities, and outcomes of COVID-19 patients. A retrospective method was used to locate data from the medical record of COVID-19 patients that were admitted to the hospital between June-October 2020. The characteristics demographics, clinical data on admission, and outcomes were extracted from the medical record. In order to determine the comorbid relationship, the chi-square test was used for the laboratory tests and clinical outcomes. A total of 120 patients were included, and more than half were male 80 (60%) with 41-60 years of age at most (51.2%). Most of the patients had comorbid diabetes mellitus (40.5%), hypertension (28.9%), and chronic lung disease (8.3%). Furthermore, most COVID-19 was severe degrees 56 (46.3%). The patients with recovery are 92 (76.0%) and only 29 (24.0%) died. The neutrophilia, and comorbid had no relationship with the clinical outcome of COVID-19 (p >0.05). The Lymphopenia and degree of severity had relationship with clinical outcome (p> 0.05). Diabetes melitus and hypertension are the most common comorbid reported in the COVID-19 patients. The Inflammation markers, such as lymphocytes, can be used as an early warning to increase awareness in treating patients with severe disease.